Regional Comparison and Strategy Recommendations of Industrial Hemp in China Based on a SWOT Analysis - Zhao, Haohan; Xiong, Heping; Chen, Jikang (Sustainability, 2021)
The hemp (Cannabis sativa L.) industry has great potential growth due to its multifaceted characteristics, however, challenged by the imbalance between the rapid agricultural production growth and the inadequate market. Against the manifesting functional overlapping and homogeneous competition among regions and nations, multi-regional synergistic development strategies of the hemp industry are critical for a sustainable agricultural-industrial system. To propose development strategies and R&D priorities of the hemp agricultural system for multi-regional synergistic development of the hemp industry. A nationwide survey and a SWOT analysis were carried out within five major production provinces in China, which is one of the largest producers of hemp, including Yunnan, Heilongjiang, Shanxi, Inner Mongolia and Jilin. Legislation, distribution, yield and utilization status and their effect on the development of industrial hemp in China were discussed. The SWOT analysis suggested that the negative effects of weaknesses and threats are stronger than the positive effects of strengths and opportunities. The modern hemp industry is still in an early phase of development characterized by the emerging legislation, growing acreage, initial researches and a few applications that pertain to mainstream use in China. Therefore, strategy recommendations, including top-level design, participating in global competition, promoting innovation and enhancing public cooperation, were proposed. We provide strategies for enhancing the hemp agricultural-industrial system, thus enabling policy makers and researchers to master the priority of promoting economic corporation and agricultural science and technology innovation.